The Influence of Compensation and Organizational Climate on Work Attitudes Mediated by Nurse Motivation at Murni Teguh Sudirman Hospital, Jakarta - Erliana, Ria; Anindita, Rina; Mustikawati, Intan Silviana (Al Makki Health Informatics Journal, 2023)
The aim of this research is to analyze the influence of compensation and organizational climate on work attitudes mediated by nurse motivation at Murni Teguh Sudirman Hospital, Jakarta. This research uses a survey method, namely research that takes samples from a population using a questionnaire as the main data collection tool to test the symptoms or phenomena observed. This research uses a causality design based on a cross-sectional time dimension, namely measurements of the independent and dependent variables are carried out simultaneously. The unit of analysis is the individual, the data analysis method uses regression. The number of samples obtained that met the inclusion criteria was 55 samples. Based on the research results, it was found that compensation, organizational climate and motivation simultaneously have an influence on work attitudes, but motivation cannot be an intervening variable. The implications of this research will theoretically prove the influence of research variables and managerially can improve the compensation system in hospitals.